Applying Community-based System Dynamics to promote child health equity: the case of healthy and fit kids in Milwaukee, WI - Greer, Yvonne D.; Nevels, Debra; Meinen, Amy; Korth, Amy L.; Moore, Travis R.; Appel, Julia; Werner, Kelsey; Calancie, Larissa; Ellis, Andre Lee; Espy, Niky; Hendricks, Shantel; Johnson, Tanya; et al. (Frontiers in Public Health, 2024)
Background: Child health equity is influenced by complex systemic factors, including structural racism, socioeconomic disparities, and access to resources. Traditional public health interventions often target individual behaviors, but there is a growing need for systems approaches that address these root causes. This study examines coalition members’ perspectives on promoting child health equity in Milwaukee as a result of participating in an intervention that includes Community-based System Dynamics (CBSD). Methods: In this case study, we used a mixed-methods approach to describe 10 coalition members’ perspective shifts over six months, after participating in CBSD activities. These activities generated a causal-loop diagram to map the systemic factors influencing child health. Data collection included pre-post interviews and surveys. The data analysis involved thematic analysis of the qualitative data from interviews, which was then integrated with the open-ended survey responses. The themes identified were cross-referenced with the causal-loop diagram factors to validate and refine the understanding of systemic influences on child health. Results: Post-intervention, coalition members shifted their focus from individual health behaviors to systemic drivers, particularly structural racism and socioeconomic disparities. The causal-loop diagram helped identify leverage points and fostered a readiness for local collective action and policy advocacy. Conclusion: Integrating CBSD into public health coalitions can shift focus from individual behaviors to systemic causes, enabling more effective interventions. This approach offers valuable insights for promoting child health equity through holistic, community-driven strategies and public policy reforms.